Design and fabrication of corn peeler / Mohamad Ariff Fikri Rahim - Rahim, Mohamad Ariff Fikri (2022)
Corn peeler machine can aid in peeling the corn more efficiently than using old method such as using knife. They are commonly being used at factory to help worker peel the corn but not at home. The objective of this project is to help people to peel the corn more with less energy used. This project used the mechanical engineering design process method. Traditional peeling method is now still being used although it is less efficient because the corn is not perfectly being cut.